PERSEPSI MASYARAKAT TENTANG PENTINGNYA PENDIDIKAN ANAK DI KECAMATAN KUBU - Nurhaliza, Mira; Hambali, Hambali; Primahardani, Indra (Komunitas Manajemen Kompetitif, 2024)
Education functions to develop skills and enhance the quality of life and human dignity, both personally and socially. In Indonesia, education is not only the responsibility of educational institutions but also of the citizens and the government. Education and society cannot be separated from each other, and the development of education is greatly influenced by the ability to adapt to changing times. This research was conducted in Kubu District, which has a lower-middle social living standard and still has children who drop out of school. The aim of this study is to understand the community's perception of the importance of children's education in Kubu District. The research method used is descriptive qualitative with purposive sampling. The sample consists of 47 people, including informants and the community of Kubu District. Data were collected through observation, interviews, questionnaires, and documentation, then analyzed using descriptive data analysis techniques and percentage techniques. The results of the study show that the majority of the Kubu District community (68%) agree that children's education is important, 21.2% are somewhat in agreement, and 10.8% disagree. Interviews indicate that economic factors, awareness of the importance of education, and adequate facilities and infrastructure are the main elements influencing the quality of children's education. Support from parents and the government is also crucial in ensuring that children achieve quality education. Overall, children's education in Kubu District is influenced by the role of parents, community awareness, government support, as well as economic factors, awareness, and infrastructure. A strong combination of these three factors will increase the likelihood of children receiving proper and quality education, and achieving a better future. Keywords: Education, Citizens, Kubu District, Quality education